Method for producing polyimide film and method for producing metal-clad laminate
By imidating polyamic acids with a specific resin composition using an infrared heater, the method addresses the challenge of achieving low CTE and uniform orientation distribution in polyimide films, effectively reducing warpage and enhancing the films' suitability for industrial applications.
Patent Information
- Application Number
- JP2020153906
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-28
- Filing Date
- 2020-09-14
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-09-14
AI Technical Summary
The existing methods for producing polyimide films by the casting method face challenges in achieving both low coefficient of thermal expansion (CTE) and uniform orientation distribution in the thickness direction, leading to potential warping issues.
The method involves imidating polyamic acids with a specific resin composition using an infrared heater for heat treatment, ensuring that at least 50 molar portions of diamine residues derived from a specific diamine compound are present per 100 molar portions of all diamine residues, which helps in achieving uniform orientation and low CTE.
This approach effectively reduces the CTE of the polyimide film to less than 20 ppm/K and minimizes warpage, making it suitable for industrial-scale production of polyimide films for various applications, including metal-clad laminates.
Smart Images

Figure 0007662314000001 
Figure 0007662314000002 
Figure 0007662314000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a polyimide film and a method for producing a metal-clad laminate. [Background technology]
[0002] Polyimide has characteristics such as high insulation, dimensional stability, easy moldability, and light weight, and is therefore widely used in electronic and electrical devices and electronic components as a material for circuit boards and the like. Polyimide is generally used in the form of a film (polyimide film) or a layer (polyimide layer) laminated on an arbitrary substrate. In the present invention, the term "polyimide film" also includes the state of a polyimide layer. As a method for forming a polyimide film, a method (so-called casting method) is known in which a resin solution of polyamic acid, which is a precursor of polyimide, is applied to a substrate to form a coating film, and the coating film is dried and imidized to obtain a polyimide film.
[0003] In the casting method, a solution of polyamic acid is applied to a substrate, dried, and cured, so the solvent evaporates only from the surface side where the substrate is not present, and in addition, only the surface side where the substrate is not present is directly exposed to heat. Therefore, on the surface (outer layer) directly exposed to heat, molecular orientation and imidization tend to progress, and the resulting polyimide film tends to have a difference in orientation distribution in the thickness direction. This tendency is particularly pronounced for resin compositions that are more likely to form orientation, i.e., have a lower coefficient of thermal expansion (CTE).
[0004] Patent Document 1 proposes that a coating film of polyamic acid produced by a casting method be thermally cured using far infrared rays in order to uniformly imidize the coating film in a short period of time.
[0005] In copper-clad laminates (CCL) using polyimide, the insulating resin layer has a three-layer structure of bottom layer / base layer / top layer, and the thickness of the bottom layer and top layer are intentionally changed to suppress the occurrence of warping when the base layer has orientation distribution. For this reason, it is necessary to provide bottom and top layers with a certain thickness or more, which makes it difficult to make the insulating resin layer thinner or to design with an emphasis on the properties of the resin that makes up the base layer.
[0006] As an evaluation of the orientation distribution, it is effective to evaluate the warpage of a single polyimide film. This is because the orientation distribution in the thickness direction also causes a distribution in the CTE in the thickness direction, and warpage occurs due to thermal contraction during cooling. Patent Document 2 proposes a flexible metal laminate having a single polyimide layer obtained by using a specific acid anhydride component and a diamine component as raw materials as a flexible metal laminate having excellent high-temperature processability and good adhesion, but does not take into account the orientation distribution in the thickness direction of the polyimide layer. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2006-192861 A [Patent Document 2] JP 2010-53322 A Summary of the Invention [Problem to be solved by the invention]
[0008] As described above, in the polyimide films prepared by the casting method, there is a trade-off between low CTE and uniform orientation distribution in the thickness direction of the film. Therefore, an object of the present invention is to provide a method for producing a polyimide film by a casting method, which achieves both a low CTE and a uniform orientation distribution in the thickness direction of the film. [Means for solving the problem]
[0009] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by imidizing a polyamic acid having a specific resin composition using an infrared heater as a heat treatment means, and have thus completed the present invention.
[0010] That is, the method for producing a polyimide film of the present invention is a method for producing a polyimide film comprising the steps of applying a solution of a polyamic acid containing a diamine residue derived from a diamine component and an acid anhydride residue derived from an acid anhydride component onto a substrate, and imidizing the solution by heat treatment with an infrared heater to form a polyimide film whose resin component is a non-thermoplastic polyimide. The method for producing a polyimide film of the present invention is characterized in that the diamine residue derived from the diamine compound represented by the following general formula (1) is 50 molar parts or more per 100 molar parts of all diamine residues contained in the non-thermoplastic polyimide.
[0011] [ka]
[0012] In formula (1), the linking group Z represents a single bond or -COO-; Y independently represents a monovalent hydrocarbon group having 1 to 3 carbon atoms which may be substituted with a halogen atom or a phenyl group, an alkoxy group having 1 to 3 carbon atoms, a perfluoroalkyl group having 1 to 3 carbon atoms, or an alkenyl group; n represents an integer of 1 or 2; and p and q independently represent integers of 0 to 4.
[0013] In the method for producing a polyimide film of the present invention, the diamine residue derived from the diamine compound represented by the general formula (1) may be within a range of 50 to 99 parts by mole, and the diamine residue derived from the diamine compound represented by the following general formula (2) may be within a range of 1 to 50 parts by mole, relative to 100 parts by mole of all diamine residues contained in the non-thermoplastic polyimide.
[0014] [ka]
[0015] In formula (2), R independently represents a halogen atom, an alkyl group or an alkoxy group having 1 to 6 carbon atoms which may be substituted with a halogen atom, or a phenyl group or a phenoxy group which may be substituted with a monovalent hydrocarbon group or an alkoxy group having 1 to 6 carbon atoms, Z1 independently represents a single bond, a divalent group selected from -O-, -S-, -CH2-, -CH(CH3)-, -C(CH3)2-, -CO-, -SO2-, or -NH-, n3 independently represents an integer of 0 to 4, and n4 independently represents an integer of 0 to 2. However, at least one of Z1 independently represents a divalent group selected from -O-, -S-, -CH2-, -CH(CH3)-, -C(CH3)2-, -CO-, -SO2-, or -NH-.
[0016] In the method for producing a polyimide film of the present invention, the diamine compound represented by the general formula (1) may be a diamine compound represented by the following general formula (A1).
[0017] [ka] In the general formula (A1), X independently represents an alkyl group having 1 to 3 carbon atoms which may be substituted with a fluorine atom; n1 and n2 independently represent an integer of 1 to 4.
[0018] In the method for producing a polyimide film of the present invention, the amount of BPDA residues derived from 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) may be within the range of 20 to 70 parts by mole per 100 parts by mole of all acid anhydride residues contained in the non-thermoplastic polyimide.
[0019] In the method for producing a polyimide film of the present invention, the polyimide film may have a coefficient of thermal expansion (CTE) of less than 20 ppm / K, and may have an average warpage of 15 mm or less when a 50 mm square polyimide film after 20 hours of humidity conditioning is left at 23°C and 50% humidity so that a convex surface at the center of the polyimide film is in contact with a flat surface and the average lift amount of the four corners is taken as the average warpage amount.
[0020] In the method for producing a polyimide film of the present invention, the thickness of the polyimide film may be within the range of 5 to 80 μm.
[0021] In the method for producing a polyimide film of the present invention, the heat treatment may be carried out on the substrate.
[0022] The method for producing a metal-clad laminate of the present invention is a method for producing a metal-clad laminate comprising an insulating resin layer and a metal layer laminated on one or both sides of the insulating resin layer. In the method for producing a metal-clad laminate of the present invention, the insulating resin layer has a polyimide layer whose resin component is made of a non-thermoplastic polyimide. In addition, the method for producing a metal-clad laminate of the present invention includes a step of directly or indirectly laminating a polyamic acid containing a diamine residue derived from a diamine component and an acid anhydride residue derived from an acid anhydride component onto a metal foil, and then imidizing the polyimide layer by heat treatment with an infrared heater. The method for producing a metal-clad laminate of the present invention is characterized in that the diamine residues derived from a diamine compound represented by the following general formula (1) are 50 molar parts or more per 100 molar parts of all diamine residues contained in the non-thermoplastic polyimide.
[0023] [ka] In formula (1), the linking group Z represents a single bond or -COO-; Y independently represents a monovalent hydrocarbon group having 1 to 3 carbon atoms which may be substituted with a halogen atom or a phenyl group, an alkoxy group having 1 to 3 carbon atoms, a perfluoroalkyl group having 1 to 3 carbon atoms, or an alkenyl group; n represents an integer of 1 or 2; and p and q independently represent integers of 0 to 4. Effect of the Invention
[0024] According to the present invention, by imidizing a polyamic acid having a specific resin composition using an infrared heater as a means of heat treatment, it is possible to achieve both a low CTE and a uniform orientation distribution of the polyimide film. In addition, the method of the present invention is also applicable to the production of, for example, a single-layer polyimide film for CCL, a single-layer polyimide film for POP (package-on-package), a single-layer polyimide film for semi-additive (SAP), etc. Therefore, the method of the present invention is particularly useful in the production process of polyimide films on an industrial scale, and has high utility value. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] A method for producing a polyimide film according to one embodiment of the present invention includes the steps of: (1) a coating film forming step of forming a coating film by applying a polyamic acid solution to a substrate; (2) a first heat treatment step of subjecting the coating film to a heat treatment and drying it; (3) a second heat treatment step in which the dried coating film is heat-treated with an infrared heater to imidize the polyamic acid and form a polyimide film; may include.
[0026] When multiple polyimide layers are laminated, the coating film forming step and the first heat treatment step can be repeatedly performed before the second heat treatment step. That is, it is preferable to repeat the steps of applying a polyamic acid solution to a substrate and drying it multiple times to form a laminate of multiple coating films, and then perform the second heat treatment step to imidize the polyamic acid in the multiple coating films all at once. In this case, it is sufficient that one layer among the multiple polyimide layers is a polyimide film manufactured by the method of the present embodiment.
[0027] Each step will now be described in detail.
[0028] [Coating film formation process] In the coating film forming step, a coating film is formed by applying a polyamic acid solution onto a substrate.
[0029] Examples of the substrate that can be used include metal foils such as copper foil, glass plates, and resin sheets such as polyimide films, polyamide films, and polyester films.
[0030] Polyamic acid, which is a precursor of polyimide, can be obtained, for example, by dissolving the raw material monomers, an acid dianhydride and a diamine compound, in approximately equimolar amounts in an organic solvent and stirring the mixture at a temperature in the range of 0 to 100°C for 30 minutes to 24 hours to cause a polymerization reaction.
[0031] The raw material monomers, the acid dianhydride and the diamine compound, can be those mentioned in the description of the non-thermoplastic polyimide described later. The composition ratio of the raw material monomers is the same as the composition ratio of the acid anhydride residue and the diamine residue contained in the non-thermoplastic polyimide. In the present invention, the acid anhydride residue represents a tetravalent group derived from a tetracarboxylic dianhydride, and the diamine residue represents a divalent group derived from a diamine compound.
[0032] Examples of organic solvents used in the polymerization reaction of polyamic acid include N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diglyme, triglyme, and cresol. Two or more of these solvents can be used in combination, and aromatic hydrocarbons such as xylene and toluene can also be used in combination. The amount of organic solvent used is not particularly limited, but it is preferable to adjust the amount of organic solvent used so that the concentration of the polyamic acid solution obtained by the polymerization reaction is about 5 to 30% by weight.
[0033] The synthesized polyamic acid can usually be used as a reaction solvent solution, but if necessary, it can be concentrated, diluted, or replaced with another organic solvent. Any of these can be used as the solution of the polyamic acid of the present embodiment.
[0034] The polyamic acid solution may contain a filler as necessary. Preferred fillers include, for example, silicon dioxide, aluminum oxide, magnesium oxide, beryllium oxide, boron nitride, aluminum nitride, silicon nitride, aluminum fluoride, calcium fluoride, etc. These may be used alone or in combination of two or more.
[0035] The method for applying the polyamic acid solution onto the substrate is not particularly limited, and it is preferable to use a coater such as a comma, die, knife or lip coater.
[0036] The viscosity of the polyamic acid solution is preferably within the range of, for example, 500 cps to 100,000 cps. If it is outside this range, defects such as uneven thickness and streaks are likely to occur in the film during coating operation using a coater or the like.
[0037] The thickness of the coating film in the coating film formation step is not particularly limited as it can be appropriately set depending on the thickness of the polyimide film to be finally obtained. However, it is preferable to coat the film so that the thickness after imidization (i.e., the thickness of the polyimide film) is preferably within a range of 5 to 80 μm, more preferably within a range of 25 to 50 μm.
[0038] [First heat treatment process] The first heat treatment step is a step of subjecting the coating film to a heat treatment to dry off the solvent. The heating means in the first heat treatment step is not particularly limited as long as it can heat the coating film to a predetermined temperature, and preferable examples include heat drying with hot air (hot air drying), heat drying with an infrared heater, etc. As conditions in the first heat treatment step, the heating temperature is preferably within the range of, for example, 80 to 160° C., and the heating time is preferably within the range of 30 seconds to 6 minutes. In this specification, the terms "heat treatment temperature" and "heating temperature" refer to the temperature of the substrate in a heat treatment container, unless otherwise specified.
[0039] [Second heat treatment process] In the second heat treatment step, the dried coating film is heat-treated to imidize the polyamic acid to form a polyimide film whose resin component is polyimide. An infrared heater is used for the heat treatment in this step. Since infrared rays can uniformly heat the coating film in the thickness direction, imidization proceeds uniformly in the thickness direction of the coating film. Therefore, imidization proceeds from the surface side of the coating film, unlike hot air, and there is no difference in the orientation distribution in the thickness direction. Therefore, by using an infrared heater, the orientation distribution of the polyimide film can be made uniform. In addition, infrared heaters are space-saving and can heat evenly in the thickness direction in a short time.
[0040] From the viewpoint of efficient energy absorption by the coating film, the wavelength of the infrared ray is preferably, for example, within the range of 1 to 8 μm, more preferably within the range of 4 to 6 μm, as the maximum radiant energy wavelength. If the maximum radiant energy wavelength is outside the above range, the efficiency of imidization may decrease.
[0041] As conditions for the second heat treatment step, the heating temperature is, for example, preferably within the range of 100 to 450°C, more preferably within the range of 120 to 400°C. The heat treatment time may be appropriately set depending on the thickness of the coating film, and is preferably completed within 3 hours, for example, at the above heating temperature, more preferably within 60 minutes. The heat treatment is preferably performed by gradually increasing the temperature within the above temperature range.
[0042] In this step, it is preferable to imidize the polyamic acid on the substrate, since the polyamic acid coating film is imidized while being fixed to the substrate, and thus it is possible to suppress the expansion and contraction changes of the formed polyimide film and maintain the thickness and dimensional accuracy of the polyimide film.
[0043] The polyimide film obtained by the above steps has a resin component made of a non-thermoplastic polyimide described below, has a low CTE, and is suppressed in warping. Note that the polyimide film produced by the method of the present embodiment is a single layer, and in the case of a structure in which multiple polyimide layers are laminated, it is sufficient that one layer among the multiple polyimide layers is a polyimide film produced by the method of the present embodiment.
[0044] <Non-thermoplastic polyimide> The non-thermoplastic polyimide constituting the polyimide film contains 50 or more molar parts of diamine residues derived from a diamine compound represented by the following general formula (1) per 100 molar parts of all diamine residues contained therein.
[0045] [ka]
[0046] In formula (1), the linking group Z represents a single bond or -COO-, Y represents a monovalent hydrocarbon group having 1 to 3 carbon atoms which may be substituted with a halogen atom or a phenyl group, an alkoxy group having 1 to 3 carbon atoms, a perfluoroalkyl group having 1 to 3 carbon atoms, or an alkenyl group, n represents an integer of 1 or 2, and p and q independently represent integers of 0 to 4. The "diamine compound" may have hydrogen atoms in the two amino groups at the terminals substituted, for example, -NR1R2 (wherein R1 and R2 independently represent any substituent such as an alkyl group).
[0047] The diamine residue derived from the diamine compound represented by the general formula (1) easily forms an ordered structure and reduces the CTE, thereby improving the dimensional stability. In addition, since it contains two or more benzene rings, it is advantageous in terms of improving the dimensional stability to reduce the imide group concentration and contribute to low moisture absorption. From this viewpoint, it is preferable that the diamine residue derived from the diamine compound represented by the general formula (1) is contained in the range of 60 to 100 molar parts relative to 100 molar parts of the total diamine residues contained in the non-thermoplastic polyimide. If the diamine residue derived from the diamine compound represented by the general formula (1) is less than 50 molar parts, the CTE increases and the dimensional stability deteriorates.
[0048] Preferred specific examples of the diamine residue derived from the diamine compound represented by general formula (1) include diamine residues derived from diamine compounds such as 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), 2,2'-diethyl-4,4'-diaminobiphenyl (m-EB), 2,2'-diethoxy-4,4'-diaminobiphenyl (m-EOB), 2,2'-dipropoxy-4,4'-diaminobiphenyl (m-POB), 2,2'-n-propyl-4,4'-diaminobiphenyl (m-NPB), 2,2'-divinyl-4,4'-diaminobiphenyl (VAB), 4,4'-diaminobiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (TFMB), and 4,4''-diamino-p-terphenyl (DATP). Among these, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), 2,2'-diethyl-4,4'-diaminobiphenyl (m-EB), 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (TFMB), and 4,4''-diamino-p-terphenyl (DATP) are preferred, and 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB) is particularly preferred because it is likely to form an ordered structure, reduces the imide group concentration, and reduces the moisture absorption rate.
[0049] The diamine compound represented by the general formula (1) is more preferably a diamine compound represented by the following general formula (A1).
[0050] [ka]
[0051] In the general formula (A1), X independently represents an alkyl group having 1 to 3 carbon atoms which may be substituted with a fluorine atom; n1 and n2 independently represent an integer of 1 to 4.
[0052] The diamine compound represented by general formula (A1) has a biphenyl skeleton and a substituent in the side chain that is effective in suppressing molecular motion, which contributes to lowering the CTE of the polyimide film. In addition, a resin composition containing 50 or more mole parts of diamine residues derived from the diamine compound represented by general formula (A1) per 100 mole parts of all diamine residues prevents excessive molecular orientation, so that heat treatment with an infrared heater can achieve both a low CTE and suppression of warpage by reducing the orientation distribution.
[0053] The non-thermoplastic polyimide preferably contains a diamine residue derived from a diamine compound represented by the following general formula (2).
[0054] [ka]
[0055] In formula (2), R independently represents a halogen atom, an alkyl group or an alkoxy group having 1 to 6 carbon atoms which may be substituted with a halogen atom, or a phenyl group or a phenoxy group which may be substituted with a monovalent hydrocarbon group or an alkoxy group having 1 to 6 carbon atoms, Z1 independently represents a single bond, a divalent group selected from -O-, -S-, -CH2-, -CH(CH3)-, -C(CH3)2-, -CO-, -SO2-, or -NH-, n3 independently represents an integer of 0 to 4, and n4 independently represents an integer of 0 to 2. However, at least one of Z1 independently represents a divalent group selected from -O-, -S-, -CH2-, -CH(CH3)-, -C(CH3)2-, -CO-, -SO2-, or -NH-.
[0056] The diamine residue derived from the diamine compound represented by the general formula (2) has a flexible site, and therefore can impart flexibility to the polyimide film. From this viewpoint, the diamine residue derived from the diamine compound represented by the general formula (2) is preferably contained within the range of 1 to 50 molar parts, more preferably within the range of 1 to 40 molar parts, relative to 100 molar parts of the total diamine residues contained in the non-thermoplastic polyimide. If the diamine residue derived from the diamine compound represented by the general formula (2) is contained in an amount exceeding 50 molar parts, the CTE increases and the dimensional stability deteriorates. In addition, if the content is less than 1 molar part, the flexibility deteriorates, and therefore the bending property deteriorates. In addition, when the non-thermoplastic polyimide contains both a diamine residue derived from the diamine compound represented by the above general formula (1) and a diamine residue derived from the diamine compound represented by the general formula (2), the content of the diamine residue derived from the diamine compound represented by the general formula (1) is more preferably within the range of 50 to 99 molar parts, and most preferably within the range of 60 to 99 molar parts, per 100 molar parts of all diamine residues contained in the non-thermoplastic polyimide.
[0057] Preferable specific examples of the diamine compound represented by the general formula (2) include, for example, 3,3'-diaminodiphenylmethane, 3,3'-diaminodiphenylpropane, 3,3'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl ether (4,4'-DAPE), 3,3-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylpropane, and 3,4'-diaminodiphenyl sulfide. , 3,4'-Diaminobenzophenone, (3,3'-bisamino)diphenylamine, 1,4-Bis(3-aminophenoxy)benzene, 1,3-Bis(4-aminophenoxy)benzene (TPE-R), 1,4-Bis(4-aminophenoxy)benzene (TPE-Q), 3-[4-(4-aminophenoxy)phenoxy]benzenamine, 3-[3-(4-aminophenoxy)phenoxy]benzenamine, 1,3-Bis(3-aminophenoxy)benzene (APB), 4,4'-[2-methyl-(1,3-phenylene bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]propane, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)]benzophenone, bis[4,4' ...)phenyl]benzophenone, bis[4,4'-(3-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)phenyl]ether 4-[3-[4-(4-aminophenoxy)phenoxy]phenoxy]aniline, 4,4'-[oxybis(3,1-phenyleneoxy)]bisaniline, bis[4-(4-aminophenoxy)phenyl]ether (BAPE), bis[4-(4-aminophenoxy)phenyl]ketone (BAPK), bis[4-(3-aminophenoxy)]biphenyl, bis[4-(4-aminophenoxy)]biphenyl, 2,2-bis(4-aminophenoxyphenyl)propane (BAPP), and the like.Among these, those in which n3 in general formula (2) is 0 are preferred, such as 4,4'-diaminodiphenyl ether (4,4'-DAPE), 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,3-bis(3-aminophenoxy)benzene (APB), 1,4-bis(4-aminophenoxy)benzene (TPE-Q), and 2,2-bis(4-aminophenoxyphenyl)propane (BAPP).
[0058] However, as long as the object of the present invention is not hindered, it is also possible to use other diamines that are commonly used as raw materials for polyimides, such as p-phenylenediamine (p-PDA) and m-phenylenediamine (m-PDA).
[0059] The acid anhydride residue contained in the non-thermoplastic polyimide is not particularly limited, but for example, an acid anhydride residue derived from pyromellitic dianhydride (PMDA) (hereinafter also referred to as PMDA residue) is preferably mentioned. Among acid anhydride residues, PMDA residue has one benzene ring, so it can increase the imide group concentration, and is an acid anhydride residue that is advantageous in reducing CTE. In addition, an acid anhydride residue derived from 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) (hereinafter also referred to as BPDA residue) is also preferably mentioned. BPDA residue has a biphenyl structure, easily forms an ordered structure, can reduce CTE, and is an acid anhydride that is advantageous in improving dimensional stability because it reduces the imide group concentration and contributes to low moisture absorption compared to PMDA residue. In addition, since it contains two or more benzene rings, it is advantageous in improving dimensional stability because it reduces the imide group concentration and contributes to low moisture absorption. In particular, the BPDA residue is preferably contained in the range of 20 to 70 molar parts, more preferably 20 to 50 molar parts, per 100 molar parts of the total acid anhydride residues contained in the non-thermoplastic polyimide. If the content of the BPDA residue is less than 20 molar parts, the moisture absorption rate tends to deteriorate and the dimensional stability tends to deteriorate. If the content of the BPDA residue is more than 70 molar parts, the CTE tends to increase and the dimensional stability tends to deteriorate.
[0060] Examples of other acid anhydride residues contained in the non-thermoplastic polyimide include 2,3',3,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-, 2,3,3',4'- or 3,3', 4,4'-Benzophenone tetracarboxylic dianhydride, 2,3',3,4'-diphenyl ether tetracarboxylic dianhydride, bis(2,3-dicarboxyphenyl) ether dianhydride, 3,3'',4,4''-, 2,3,3'',4''- or 2,2'',3,3''-p-terphenyl tetracarboxylic dianhydride, 2,2-bis(2,3- or 3,4-dicarboxyphenyl)-propane dianhydride, bis(2,3- or 3.4-dicarboxyphenyl)methane dianhydride, bis(2,3- or 3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3- or 3,4-dicarboxyphenyl)ethane dianhydride, 1,2,7,8-, 1,2,6,7- or 1,2,9,10-phenanthrene-tetracarboxylic dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)tetrafluoropropane dianhydride, 2,3,5,6-cyclohexane dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-1,2,5,6-tetracarboxylic acid Examples of the acid anhydride residues include those derived from aromatic tetracarboxylic dianhydrides such as 2,6- or 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-(or 1,4,5,8-)tetrachloronaphthalene-1,4,5,8-(or 2,3,6,7-)tetracarboxylic dianhydride, 2,3,8,9-, 3,4,9,10-, 4,5,10,11- or 5,6,11,12-perylene-tetracarboxylic dianhydride, cyclopentane-1,2,3,4-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, pyrrolidine-2,3,4,5-tetracarboxylic dianhydride, thiophene-2,3,4,5-tetracarboxylic dianhydride, and 4,4'-bis(2,3-dicarboxyphenoxy)diphenylmethane dianhydride.
[0061] By selecting the types of the acid anhydrides and diamines, or by selecting the molar ratio of each of two or more types of acid anhydrides or diamines when using two or more types of acid anhydrides or diamines, it is possible to control the physical properties such as thermal expansion and orientation of the non-thermoplastic polyimide.
[0062] In the case where the non-thermoplastic polyimide has a plurality of polyimide structural units, they may be present as blocks or randomly, but are preferably present randomly.
[0063] The imide group concentration of the non-thermoplastic polyimide is preferably 35% by weight or less. Here, "imide group concentration" means the value obtained by dividing the molecular weight of the imide group (-(CO)2-N-) in the polyimide by the molecular weight of the entire polyimide structure. If the imide group concentration exceeds 35% by weight, the molecular weight of the resin itself decreases, and the low moisture absorption property also deteriorates due to the increase in polar groups. By selecting the above combination of the acid anhydride and the diamine compound, the molecular orientation in the non-thermoplastic polyimide is controlled, thereby suppressing the increase in CTE associated with the decrease in the imide group concentration and ensuring low moisture absorption.
[0064] The weight-average molecular weight of the non-thermoplastic polyimide is preferably within the range of 10,000 to 400,000, and more preferably within the range of 50,000 to 350,000. If the weight-average molecular weight is less than 10,000, the strength of the polyimide film tends to decrease and become brittle. On the other hand, if the weight-average molecular weight exceeds 400,000, the viscosity increases excessively, and defects such as uneven thickness and streaks tend to occur during coating.
[0065] <cte> The polyimide film produced by the method of the present embodiment has a low CTE achieved by heating the polyamic acid of the above resin composition with an infrared heater. The CTE of the polyimide film is preferably less than 20 ppm / K, and more preferably 18 ppm / K or less. If the CTE is 20 ppm / K or more, for example, when the polyimide film is combined with a metal layer to form a metal-clad laminate, warping is likely to occur, or the dimensional stability is reduced when the metal layer is etched and patterned.
[0066] <Warping> The polyimide film produced by the method of the present embodiment has a uniform orientation distribution and effectively reduces warpage by heating the polyamic acid of the above resin composition with an infrared heater. The average warpage of the polyimide film is 15 mm or less, preferably 10 mm or less, when the polyimide film is left at rest with the central convex surface of a 50 mm square film in contact with a flat surface after 20 hours of humidity conditioning under conditions of 23°C and 50% humidity, and the average lift amount of the four corners is taken as the average warpage amount, for example.
[0067] <Thickness> The thickness of the polyimide film produced by the method of the present embodiment is preferably within a range of 5 to 80 μm, more preferably within a range of 25 to 50 μm, from the viewpoint of insulation properties when used as an insulating layer of a circuit board. The polyimide film produced by the method of the present embodiment can be formed into a laminate structure with other resin layers as necessary.
[0068] The polyimide film produced by the method of the present embodiment has a low CTE and suppressed warpage, and therefore can be preferably used for applications such as a single-layer polyimide film for CCL, a single-layer polyimide film for POP (package-on-package), and a single-layer polyimide film for semi-additive (SAP). Therefore, the method of the present embodiment is particularly useful in an industrial-scale production process of polyimide films, and has high utility value.
[0069] [Metal-clad laminate] The metal-clad laminate of the present embodiment comprises an insulating resin layer and a metal layer provided on at least one surface of the insulating resin layer, and the polyimide layer constituting a part or all of the insulating resin layer may be formed from a polyimide film obtained by the manufacturing method of the above embodiment.
[0070] The material of the metal layer is not particularly limited, but examples thereof include copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese, and alloys thereof. Among these, copper or a copper alloy is particularly preferred. The material of the wiring layer in the circuit board described later is the same as that of the metal layer.
[0071] The thickness of the metal layer is not particularly limited, but when a metal foil such as copper foil is used, the thickness is preferably 35 μm or less, more preferably within the range of 5 to 25 μm. From the viewpoint of production stability and handling, the lower limit of the thickness of the metal foil is preferably 5 μm. When copper foil is used, it may be rolled copper foil or electrolytic copper foil. In addition, commercially available copper foil may be used as the copper foil.
[0072] The metal foil may be subjected to a surface treatment using, for example, siding, aluminum alcoholate, aluminum chelate, a silane coupling agent, or the like, for the purpose of, for example, rust prevention or improving adhesive strength.
[0073] [Circuit board] The metal-clad laminate of the above embodiment is useful mainly as a circuit board material for FPC, etc. That is, a circuit board can be manufactured by processing the metal layer of the metal-clad laminate into a pattern by a conventional method to form a wiring layer. EXAMPLES
[0074] The features of the present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to the examples. In the following examples, various measurements and evaluations are as follows, unless otherwise specified.
[0075] [Measurement of coefficient of thermal expansion (CTE)] The thermal expansion coefficient was measured by using a thermomechanical analyzer (manufactured by Bruker, product name: 4000SA) to heat a polyimide film measuring 3 mm x 20 mm at a constant heating rate from 30°C to 250°C while applying a load of 5.0 g, and then holding the film at that temperature for 10 minutes. The film was then cooled at a rate of 5°C / min to determine the average thermal expansion coefficient from 250°C to 100°C.
[0076] [Measurement of storage modulus] The storage modulus was measured by heating a 5 mm x 20 mm polyimide film in an oven at 120°C for 2 hours and at 170°C for 3 hours, and then heating it stepwise from 30°C to 400°C at a heating rate of 4°C / min using a dynamic viscoelasticity device (DMA: manufactured by UBM, product name: E4000F) at a frequency of 11 Hz. The storage modulus at 30°C was 1.0 x 10 9 Pa or more, and the storage modulus at 350°C is 1.0×10 8 Polyimide with a storage modulus of 1.0×10 Pa or more at 30°C is considered non-thermoplastic. 9 Pa or more, and the storage modulus at 350°C is 1.0×10 8 Polyimides with a modulus of less than 1 Pa are considered thermoplastic.
[0077] [Warpage measurement] The warping of the polyimide film was measured by conditioning a 50 mm x 50 mm polyimide film for 20 hours under conditions of 23°C and 50% humidity, then placing the sample so that the convex surface at the center was in contact with a flat surface, measuring the distance from the surface to which the sample was placed at each of the four corners, and averaging the distances to obtain the average amount of warping.
[0078] [Measurement of copper foil surface roughness] The surface roughness of the copper foil was measured in tapping mode using an AFM (manufactured by Bruker AXS, product name: Dimension Icon SPM) and a probe (manufactured by Bruker AXS, product name: TESPA (NCHV), tip curvature radius 10 nm, spring constant 42 N / m) over an area of 80 μm × 80 μm on the copper foil surface, and the ten-point average roughness (Rzjis) was calculated.
[0079] The abbreviations used in the Examples and Reference Examples represent the following compounds. m-TB: 2,2'-dimethyl-4,4'-diaminobiphenyl DAPE: 4,4'-diaminodiphenyl ether PMDA: Pyromellitic dianhydride BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride TFMB: 2,2'Bis(trifluoromethyl)benzidine TPE-R: 1,3-bis(4-aminophenoxy)benzene p-PDA: p-phenylenediamine BAPP: 2,2-bis(4-aminophenoxyphenyl)propane DMAc: N,N-dimethylacetamide
[0080] (Synthesis Example 1) Under a nitrogen gas flow, 14.472 g of DAPE (0.0723 mol) and 170 g of DMAc were added to a 300 ml separable flask so that the solid content concentration was 15 wt %, and the mixture was stirred at room temperature to dissolve. Next, 15.528 g of PMDA (0.0712 mol) was added, and the mixture was stirred at room temperature for 3 hours to carry out a polymerization reaction, thereby preparing polyamic acid solution 1.
[0081] (Synthesis Example 2) Under a nitrogen gas flow, 8.139g of DAPE (0.0407 mol), 4.296g of p-PDA (0.0407 mol) and 170g of DMAc were added to a 300ml separable flask so that the solid content concentration was 15% by weight, and the mixture was stirred at room temperature to dissolve. Next, 17.466g of PMDA (0.0801 mol) was added, and the mixture was stirred at room temperature for 3 hours to carry out a polymerization reaction, preparing polyamic acid solution 2.
[0082] (Synthesis Example 3) Under a nitrogen stream, 8.995 g of p-PDA (0.0832 mol) and 170 g of DMAc were added to a 300 ml separable flask so that the solid content concentration was 15 wt%, and the mixture was stirred at room temperature to dissolve. Next, 12.07 g of BPDA (0.041 mol) and 8.935 g of PMDA (0.041 mol) were added, and the mixture was stirred at room temperature for 3 hours to carry out a polymerization reaction, preparing polyamic acid solution 3.
[0083] (Synthesis Example 4) Under a nitrogen flow, 7.385g of DAPE (0.0369 mol), 3.988g of p-PDA (0.03688 mol) and 170g of DMAc were added to a 300ml separable flask so that the solid content concentration was 15% by weight, and the mixture was stirred at room temperature to dissolve. Next, 10.704g of BPDA (0.0363 mol) and 7.923g of PMDA (0.0363 mol) were added, and the mixture was stirred at room temperature for 3 hours to carry out a polymerization reaction, preparing polyamic acid solution 4.
[0084] (Synthesis Example 5) Under a nitrogen flow, 2.883g of DAPE (0.0144 mol), 6.227g of p-PDA (0.0576 mol) and 170g of DMAc were added to a 300ml separable flask so that the solid content concentration was 15% by weight, and the mixture was stirred at room temperature to dissolve. Next, 20.891g of BPDA (0.0709 mol) was added, and the mixture was stirred at room temperature for 3 hours to carry out a polymerization reaction, preparing polyamic acid solution 5.
[0085] (Synthesis Example 6) Under a nitrogen gas flow, 7.13 g of DAPE (0.0356 mol), 7.571 g of m-TB (0.0356 mol) and 170 g of DMAc were added to a 300 ml separable flask so that the solid content concentration was 15 wt%, and the mixture was stirred at room temperature to dissolve. Next, 15.3 g of PMDA (0.0701 mol) was added, and the mixture was stirred at room temperature for 3 hours to carry out a polymerization reaction, preparing polyamic acid solution 6.
[0086] (Synthesis Example 7) Under a nitrogen flow, 1.947g of TPE-R (0.0066 mol), 12.745g of m-TB (0.0599 mol) and 170g of DMAc were added to a 300ml separable flask so that the solid content concentration was 15% by weight, and the mixture was stirred at room temperature to dissolve. Next, 3.86g of BPDA (0.0131 mol) and 11.447g of PMDA (0.0525 mol) were added, and the mixture was stirred at room temperature for 3 hours to carry out a polymerization reaction, preparing polyamic acid solution 7.
[0087] (Synthesis Example 8) Under a nitrogen flow, 13.707 g of m-TB (0.0646 mol) and 170 g of DMAc were added to a 300 ml separable flask so that the solid content concentration was 15 wt%, and the mixture was stirred at room temperature to dissolve. Next, 9.356 g of BPDA (0.0318 mol) and 6.936 g of PMDA (0.0318 mol) were added, and the mixture was stirred at room temperature for 3 hours to carry out a polymerization reaction, preparing polyamic acid solution 8.
[0088] (Synthesis Example 9) Under a nitrogen gas flow, 6.299g of DAPE (0.0315 mol), 10.087g of TFMB (0.0315 mol) and 170g of DMAc were added to a 300ml separable flask so that the solid content concentration was 15% by weight, and the mixture was stirred at room temperature to dissolve. Next, 13.613g of PMDA (0.0624 mol) was added, and the mixture was stirred at room temperature for 3 hours to carry out a polymerization reaction, thereby preparing polyamic acid solution 9.
[0089] (Synthesis Example 10) Under a nitrogen gas flow, 26.44 g of BAPP (0.0636 mol) and 170 g of DMAc were added to a 300 ml separable flask so that the solid content concentration was 15 wt %, and the mixture was stirred at room temperature to dissolve. Next, 18.56 g of BPDA (0.063 mol) was added, and the mixture was stirred at room temperature for 3 hours to carry out a polymerization reaction, thereby preparing a polyamic acid solution 10.
[0090] (Reference example 1) Polyamic acid solution 1 was uniformly applied to copper foil 1 (electrolytic copper foil, thickness: 12 μm, Rzjis: 0.6 μm) so that the thickness after curing was about 25 μm, and then heated and dried at 130 ° C to form a coating film of polyamic acid. The coating film was then subjected to stepwise heat treatment from 130 ° C to 360 ° C using an infrared heater under the condition of maximum radiant energy wavelength: 3 to 7 μm, and imidization was completed within 15 minutes. The copper foil was etched away using an aqueous ferric chloride solution to prepare polyimide film 1 (non-thermoplastic, CTE: 40.4 ppm / K). In the evaluation of the warpage of polyimide film 1, the warpage was large and cylindrical, making it impossible to measure the warpage. The results are shown in Table 1.
[0091] (Reference Examples 2 to 5, Examples 1 to 4) Polyimide films 2 to 9 were prepared in the same manner as in Reference Example 1, except that the polyamic acid solutions shown in Table 1 were used. The CTE and warpage of the polyimide films 2 to 9 were measured, and the results are shown in Table 1.
[0092] The above results are summarized in Table 1. In addition, in the "warpage" column in Table 1, samples that became cylindrical and could not be measured are indicated as "large."
[0093] [Table 1]
[0094] From the results in Table 1, it can be seen that the polyimide films 6 to 8 of Examples 1 to 3, which contain 50 molar parts or more of m-TB per 100 molar parts of all diamine residues as the diamine component, and the polyimide film 9 of Example 4, which contains 50 molar parts or more of TFMB as the diamine component, all have a CTE of less than 20 ppm / K and a warpage of less than 15 mm. Therefore, it was confirmed that by curing the polyamic acid using these diamine compounds with an infrared heater, the gradient of the orientation state of the polyimide in the thickness direction of the polyimide layer laminated on the copper foil becomes small, thereby realizing a low CTE of the polyimide layer and suppression of warpage.
[0095] (Reference example 6) Using the polyamic acid solution 7, a coating film of polyamic acid was formed in the same manner as in Reference Example 1. The coating film was then heat-treated from 130°C to 360°C using a hot air curing oven, and imidization was completed within 15 minutes. The copper foil was removed by etching in the same manner as in Reference Example 1 to prepare a polyimide film 10 (non-thermoplastic, CTE; 16.8 ppm / K). The warp of the polyimide film 10 was 16 mm.
[0096] Example 5 The polyamic acid solution 10 was uniformly applied to the copper foil 1 so that the thickness after curing was 2.5 μm, and then heated and dried at 130 ° C. The polyamic acid solution 7 was uniformly applied thereon so that the thickness after curing was about 25 μm, and then heated and dried at 130 ° C. Furthermore, the polyamic acid solution 10 was uniformly applied thereon so that the thickness after curing was 2.5 μm, and then heated and dried at 130 ° C. to form a coating film of polyamic acid. Thereafter, the coating film was subjected to stepwise heat treatment from 130 ° C. to 360 ° C. using an infrared heater under the condition of maximum radiation energy wavelength: 3 to 7 μm, and imidization was completed within 15 minutes, and a metal-clad laminate 10 was prepared.
[0097] Although the embodiment of the present invention has been described in detail above for the purpose of illustration, the present invention is not limited to the above embodiment, and various modifications are possible.< / cte>
Claims
1. A method for producing a metal-clad laminate comprising an insulating resin layer and a metal layer laminated on one or both sides of the insulating resin layer, the insulating resin layer has a polyimide layer whose resin component is a non-thermoplastic polyimide; The method includes a step of directly or indirectly laminating a polyamic acid containing a diamine residue derived from a diamine component and an acid anhydride residue derived from an acid anhydride component on a metal foil, followed by imidization by heat treatment with an infrared heater to form the polyimide layer, A method for producing a metal-clad laminate, characterized in that, relative to 100 parts by mole of all diamine residues contained in the non-thermoplastic polyimide, a diamine residue derived from a diamine compound represented by the following general formula (1) is within a range of 50 to 99 parts by mole, and a diamine residue derived from a diamine compound represented by the following general formula (2) is within a range of 1 to 50 parts by mole. 【Chemistry 1】 [In formula (1), the linking group Z represents a single bond or -COO-, Y represents a monovalent hydrocarbon group having 1 to 3 carbon atoms, which may be substituted with a halogen atom or a phenyl group, an alkoxy group having 1 to 3 carbon atoms, a perfluoroalkyl group having 1 to 3 carbon atoms, or an alkenyl group, n represents an integer of 1 or 2, and p and q independently represent integers of 0 to 4.] 【Chemistry 2】 [In formula (2), R independently represents a halogen atom, an alkyl group or alkoxy group having 1 to 6 carbon atoms which may be substituted with a halogen atom, or a phenyl group or phenoxy group which may be substituted with a monovalent hydrocarbon group or alkoxy group having 1 to 6 carbon atoms; Z 1 independently represents a single bond, a divalent group selected from -O-, -S-, -CH 2 -, -CH(CH 3 )-, -C(CH 3 ) 2 -, -CO-, -SO 2 -, or -NH-; n 3 independently represents an integer of 0 to 4, and n 4 independently represents an integer of 1 to 2, with the proviso that at least one of Z 1 represents a divalent group selected from -O-, -S-, -CH 2 -, -CH(CH 3 )-, -C(CH 3 ) 2 -, -CO-, -SO 2 -, or -NH-.]
2. 2. The method for producing a metal-clad laminate according to claim 1, wherein the diamine compound represented by the general formula (1) is a diamine compound represented by the following general formula (A1): 【Chemistry 3】 [In general formula (A1), X independently represents an alkyl group having 1 to 3 carbon atoms which may be substituted with a fluorine atom, n 1 and n 2 each independently represents an integer of 1 to 4.
3. The method for producing a metal-clad laminate according to claim 1, characterized in that the BPDA residue derived from 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) is in the range of 20 to 70 molar parts per 100 molar parts of all acid anhydride residues contained in the non-thermoplastic polyimide.
4. 2. The method for producing a metal-clad laminate according to claim 1, characterized in that the polyimide layer has a coefficient of thermal expansion (CTE) of less than 20 ppm / K, and when a 50 mm square polyimide film is formed after 20 hours of humidity conditioning under conditions of 23°C and 50% humidity, and is left so that the convex surface at the center is in contact with a flat surface, the average amount of lift of the four corners is taken as the average amount of warping, and the average amount of warping is 15 mm or less.
5. 2. The method for producing a metal-clad laminate according to claim 1, wherein the thickness of the polyimide layer is within a range of 5 to 80 μm.
Citation Information
Patent Citations
Production of polyimide shape
JP1990138340A
Manufacturing method and equipment for flexible polyimide-metal laminate
JP2006192861A
Polyamic acid and non-thermoplastic polyimide resin
JP2010053322A
Polyimide film, metal-clad laminate, and circuit board
JP2019065266A
Polyimide film, laminate, display surface material, touch panel member, liquid crystal display device and organic electroluminescent display device
WO2019013169A1